Rurality and mobile devices: Social appropriation and use of the ICT coffee production tablet. Study case of federación nacional de cafeteros para Antioquia [Ruralidad y dispositivos móviles: Apropiación social y uso de la tableta de información cafetera TIC. Estudio de caso federación nacional de cafeteros para Antioquia] (2015)
Introduction. The incursion of ICT's, by the national government, has put in a public scenario the relationship between information, consumption and technology appropriation in the rural Colombian sector. Today, productivity and daily life if rural areas are related with the digital activities and practices. Objective. Identify the use and the appropriation of "ICT tablets" in Antioquian coffee production towns. Materials and methods. The study is classified as qualitative, as it aims to comprise an outlook of data, information and results that involve rural daily life, experiences and human relationships proper of the Antioquian coffee farmers and the use they make of the ICT tablet devices. Meetings with focus groups and conversations in rural places were made, thus evaluating and getting to know the program from the cultural and social characteristics of the farmers. Focused interviews were also made, and a content analysis instrument was designed to revise the tablet's contents and applications related to coffee farming topics. Results. 1) The dimensions of social appropriation of technology from the access, competencies, digital literacy and gender equality in the use, were demonstrated according to the UNESCO's ICT appropriation parameters. 2) The assimilation of technology is not incompatible with the daily experience of coffee farmers. The relationship is mutual, round, the device and the rural necessities coexist in harmony. Conclusion. The ICT appropriation levels achieved by coffee farmers are high, especially in those who assume the challenge of overcome fear, inexperience and lack of technological knowledge. They do want to add these technologies to their daily lives. The fact that most of coffee farmers have cellular phones and consider the "Coffee Tablet" as a valuable element for their lives and for their families, is a valuable opportunity to boost rural development and production with the use of ICT.